2005
DOI: 10.1007/s11167-005-0515-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Peat Humic Acids To Increase Their Bioactivity

Abstract: The possibility of chemical modification of peat humic acids in order to increase their bioactivity by reduction with tin(II) chloride and sodium borohydride and also by carboxylation using the Kolbe method was analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Purposeful chemical modification of HA can change their composition and increase the content of the necessary functional groups and thereby improve their PTTE sorption properties. Among various possible ways, HA can be modified by carrying out an oxidation (destroying or mild) (Schnitzer and Ortiz de Serra, 1973;Meneghel et al, 1972;Hayes and Swift, 1978;Martin et al, 1982), reduction (Lebedeva et al, 2005), or introduction of organic molecule fragments into the structure of HA (Perminova et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purposeful chemical modification of HA can change their composition and increase the content of the necessary functional groups and thereby improve their PTTE sorption properties. Among various possible ways, HA can be modified by carrying out an oxidation (destroying or mild) (Schnitzer and Ortiz de Serra, 1973;Meneghel et al, 1972;Hayes and Swift, 1978;Martin et al, 1982), reduction (Lebedeva et al, 2005), or introduction of organic molecule fragments into the structure of HA (Perminova et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the possibility of chemical modification of peat HA by reduction with SnCl 2 and NaBH 4 , and also by carboxylation using the Kolbe method was studied by Lebedeva et al (2005). The experimental results showed that during the treatment of HA by SnCl 2 in an alkaline conditions, significant structural changes occurred: quinoid groups were reduced to phenolic, the number of carboxyl groups in air did not change, and in the atmosphere of CO 2 increased.…”
Section: Introductionmentioning
confidence: 99%